2021
DOI: 10.3389/fimmu.2021.688436
|View full text |Cite
|
Sign up to set email alerts
|

Broad T Cell Targeting of Structural Proteins After SARS-CoV-2 Infection: High Throughput Assessment of T Cell Reactivity Using an Automated Interferon Gamma Release Assay

Abstract: BackgroundAdaptive immune responses to structural proteins of the virion play a crucial role in protection against coronavirus disease 2019 (COVID-19). We therefore studied T cell responses against multiple SARS-CoV-2 structural proteins in a large cohort using a simple, fast, and high-throughput approach.MethodsAn automated interferon gamma release assay (IGRA) for the Nucleocapsid (NC)-, Membrane (M)-, Spike-C-terminus (SCT)-, and N-terminus-protein (SNT)-specific T cell responses was performed using fresh w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 28 publications
(40 reference statements)
5
25
3
Order By: Relevance
“…Even so, the few mutations mostly in the RBD defining various spike variants seem unlikely to affect recognition by CD8 + T cells (51). Overall, differences from the findings of Le Bert et al and Peng et al may result primarily from evaluation of isolated CD8 + T cells versus bulk PBMC (in which CD4 + T cells typically predominate); other studies grossly comparing CD4 + T cells to CD8 + T cells have shown that the former tend to predominate (12,46,49,(52)(53)(54), and that the two do not correlate (55). Finally, our results suggest that nucleocapsid might be a useful target for vaccine inclusion to elicit broader and more durable CD8 + T cell responses, which is also supported by a recent study suggesting that immunodominant targeting of nucleocapsid is associated with better outcome after SARS-CoV-2 infection (56).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Even so, the few mutations mostly in the RBD defining various spike variants seem unlikely to affect recognition by CD8 + T cells (51). Overall, differences from the findings of Le Bert et al and Peng et al may result primarily from evaluation of isolated CD8 + T cells versus bulk PBMC (in which CD4 + T cells typically predominate); other studies grossly comparing CD4 + T cells to CD8 + T cells have shown that the former tend to predominate (12,46,49,(52)(53)(54), and that the two do not correlate (55). Finally, our results suggest that nucleocapsid might be a useful target for vaccine inclusion to elicit broader and more durable CD8 + T cell responses, which is also supported by a recent study suggesting that immunodominant targeting of nucleocapsid is associated with better outcome after SARS-CoV-2 infection (56).…”
Section: Discussionmentioning
confidence: 76%
“…Various studies reported differing results on longevity of virus-specific T cell responses (CD4 + , CD8 + or combined) after SARS-CoV-2 infection, with observations of both persistence ( 37 , 45 , 47 , 53 55 , 57 , 58 ) and decay ( 14 , 47 , 59 , 60 ). We observed decay of CD8 + T cell responses similar to our observations of anti-RBD antibodies ( 29 , 61 ), and most rapid waning of matrix responses, in agreement with Le Bert et al.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used a whole blood IFN-g and IL-2 release assay, while the cited studies used ELISPOT and flow cytometry analysis. Although ELISPOT could be considered more sensitive than the whole blood-based cytokine release assay used here, CRA has been shown to accurately assess cellular immunity to SARS-CoV-2 and vaccination (31)(32)(33)(34). Of note, Tan et al (35) performed a direct comparison between ELISPOT and CRA and found the sensitivity of the two methods are comparable with a strong positive correlation with each other.…”
Section: Discussionmentioning
confidence: 90%
“…In our study, we used a whole blood IFN-γ and IL-2 release assay, while the cited studies used ELISPOT and flow cytometry analysis. Although ELISPOT could be considered more sensitive than the whole blood-based cytokine release assay used here, CRA has been shown to accurately assess cellular immunity to SARS-CoV-2 and vaccination ( 31 34 ). Of note, Tan et al.…”
Section: Discussionmentioning
confidence: 99%
“…After two days of incubation at 37 o C plasma was recovered for analysis of interferon-γ (IFN-γ) by ELISA. This assay captures SARS-CoV-2-specific reactivity of CD4 + and CD8 + T cells with high specificity and sensitivity 9 . S1-induced IFN-γ production is presented with levels in unstimulated samples subtracted using a limit of detection of 10 pg/ml.…”
Section: To the Editormentioning
confidence: 99%